MANAGING FINANCING RISK OF ISLAMIC BANKING PRODUCTS IN INDONESIA: A VALUE AT RISK APPROACH - Sari, Nilam; Ibrahim, Azharsyah; Muzammil, Muzammil; Muksal, Muksal (Islam Futura, 2024)
This study aims to assess the potential risk and anticipated returns of equity and debt-based financing products in Islamic banking in Indonesia, represented by the three most prevalent contracts: musharakah, mudharabah, and murabahah. Data was collected from banks' monthly financial reports published on the Indonesia Financial Service Authority (OJK) website from 2014 to 2020, resulting in 82 observations. Data analysis was conducted using the Value at Risk (VaR) method with the variance-covariance approach. Among many methods, VaR is one of the most popular techniques that yields the most comprehensive results in measuring risk and return. The findings reveal that, in general, all equity and debt-based financing yielded stable risk and returns. However, equity-based financing produced higher returns, but also generated higher risks due to its uncertain nature. The results also demonstrate that risk management in Islamic banks improved gradually during the observation period, as indicated by the average score of portfolio combinations. These findings suggest that Islamic banks should balance their product offerings between equity-based financing and debt-based financing while simultaneously strengthening risk management, especially for murabahah products in equity-based financing.